1989
DOI: 10.1128/mcb.9.7.2828
|View full text |Cite
|
Sign up to set email alerts
|

Regulated expression of nuclear protein(s) in myogenic cells that binds to a conserved 3' untranslated region in pro alpha 1 (I) collagen cDNA.

Abstract: We describe the identification and DNA-binding properties of nuclear proteins from rat L6 myoblasts which recognize an interspecies conserved 3' untranslated segment of proal(I) collagen cDNA. Levels of the two prootl(I) collagen RNAs, present in L6 myoblasts, decreased drastically between 54 and 75 h after induction of myotube formation in serum-free medium. Both mRNAs contained a conserved sequence segment of 135 nucleotides (termed tame sequence) in the 3' untranslated region that had 96% homology to the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…From the Northern/dot blot double-hybridization experiment, the relative amounts of Cx40 and Cx37 transcript in hm& were estimated and used to standardize the results of both Northern blot hybridizations. The amounts of poly(A) + RNA on Northern blots were estimated by hybridization to the 1.58-kb Ez, oRI-SalI fragment of mouse cytochrome c oxidase eDNA (clone pAG82; Herget et al, 1989).…”
Section: Southern and Northern Blot Analysismentioning
confidence: 99%
“…From the Northern/dot blot double-hybridization experiment, the relative amounts of Cx40 and Cx37 transcript in hm& were estimated and used to standardize the results of both Northern blot hybridizations. The amounts of poly(A) + RNA on Northern blots were estimated by hybridization to the 1.58-kb Ez, oRI-SalI fragment of mouse cytochrome c oxidase eDNA (clone pAG82; Herget et al, 1989).…”
Section: Southern and Northern Blot Analysismentioning
confidence: 99%
“…For example, stellate cell type collagen I mRNA is stabilized after wound healing and contributes to enhanced type I collagen mRNA and protein expression (Stefanovic et al, 1997(Stefanovic et al, , 1999. In these experiments, increased mRNA stability was a result of ␣CP binding to poly(C)-rich areas of the type I collagen 3Ј UTR mRNA (Focht and Adams, 1984;Herget et al, 1989;Stefanovic et al, 1997Stefanovic et al, , 1999. Thus, our work has extended the concept that hepatic wound healing is associated with changes in mRNA stability by identifying TGF-␤, a critical cytokine involved in diverse forms of wounding (Border and Noble, 1994;Sanderson et al, 1995), as a regulator of 3Ј UTR binding proteins that contribute to mRNA stability during this process.…”
mentioning
confidence: 95%
“…Contribution of the COL1A1 Minigene 3Ј-Flanking Sequence-Several groups have examined the role of the COL1A1 3Ј-flanking and untranslated (3Ј-UTR) regions in transcriptional regulation as well as mRNA stabilization (32,33). Recently, Sokolov et al (27) reported that 90% of the 3Ј-UTR, in the context of the human COL1A1 minigene, was not essential for tissue-specific expression.…”
Section: Discussionmentioning
confidence: 99%